Tinjauan Hukum Islam Terhadap Merarik Nyongkolan (Study Kasus di Desa Bajur Kec. Labuapi Lobar) - Badarudin (STIS DAFA MATARAM, 2024)
This study examines the Merarik Nyongkolan tradition in the Sasak community of Bajur Village, Labuapi District, West Lombok, from an Islamic legal perspective. The tradition, which involves the